Prevalence and Clinical Correlates of Internet Addiction Symptoms and Their Association With Quality of Life in Adolescents With Major Depressive Disorder: A Multicenter Cross-Sectional Study - Wang, Song; Xia, Lei; Wang, Jiawei; Yuan, Xiaoping; Shi, Yudong; Wang, Xixin; Li, Xiaoyue; Hu, Yu; Zhang, Yulong; Yang, Yating; Geng, Feng; Liu, Zhiwei; et al. (Frontiers in Psychiatry, 2022)
Background Internet addiction (IA) symptoms are common among adolescents and negatively impact their academic performance and development. These symptoms are also associated with lower quality of life (QOL) and increased suicidality. This study aimed to examine the prevalence and the sociodemographic and clinical correlates of IA symptoms in adolescents with major depressive disorder (MDD) and their association with QOL. Methods This cross-sectional study was conducted in three general and four psychiatric hospitals in Anhui Province, China, from January to July 2021. Sociodemographic and clinical data were collected. The Internet Addiction Test (IAT), Center for Epidemiologic Studies of Depression Symptom Scale (CES-D), and World Health Organization Quality of Life Brief version (WHOQOL-BREF) were utilized to examine IA, depressive symptoms, and QOL, respectively. Results In a multicenter sample of 278 adolescents with MDD, the prevalence of IA symptoms in adolescents with MDD was 46.8% (95% CI: 40.9–52.7%). Logistic regression analysis showed that patients with more severe depressive symptoms (odds ratio [OR] = 1.05, 95% CI: 1.03–1.08), those living in a rural area (OR = 1.94, 95% CI: 1.15–3.27), and those with poor academic performance (OR = 2.90, 95% CI: 1.42–5.95) were more likely to have IA symptoms. After controlling for confounding factors, patients with IA symptoms had significantly poorer QOL in the physical, psychological, and environmental domains than those without IA symptoms. Conclusion IA symptoms are common in adolescents with MDD and appear to be associated with clinical symptoms. We could not infer a causal relationship between IA and depression because this was a cross-sectional study. Considering the positive association between IA symptoms and lower QOL, screening for IA symptoms should be conducted, and effective measures should be implemented for adolescents with MDD.